Living With a Stigmatized Identity; Perceptions of Disclosure, Coping, and Medication Adherence Among Adolescent Boys and Young Men in Chiredzi-Zimbabwe - Kanyemba, Roselyn; Govender, Kaymarlin; Jimu, Christopher (Frontiers in Public Health, 2021)
There is limited research on adolescent boys and young men (ABYM)'s initial and onward HIV seropositive status disclosure, coping strategies and treatment adherence journeys especially in Zimbabwe. This qualitative exploratory study employed in-depth individual interviews at Chiredzi General Hospital in Zimbabwe to explore the dynamics of disclosure, coping and treatment adherence among ABYM. Twenty-one HIV positive ABYM with ages ranging from 14 to 21 were recruited from their scheduled visit to collect medication at the hospital. Findings indicate that ABYM disclosure journeys began with shock, confusion or misunderstanding and ended in a positive life outlook. Treatment adherence among ABYM was very poor due to poverty, erratic food supply, feeling sick after taking medication, forgetfulness and the public nature of medication collection centers. The study concluded that ABYM maintained secrecy in order to be accepted by their peers but also to protect themselves from stigma and isolation.